2019
DOI: 10.1039/c9sc02818h
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-mediated deuteration of silanes with deuterium oxide

Abstract: An unprecedented visible-light-mediated metal-free deuteration of hydrosilanes using D2O as a deuterium source was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…This amine is then oxidized via as ingle electron transfer (SET) from the excited photocatalyst (E 1/2 {*Ir III /Ir II } =+1.51 Vand E 1/2 {nBuNH 2 } % + 1.40 V) [18] to generatet he a-amino radical 5, which then undergoes aH AT process with the deuterated thiol (generated in situ) to form the deuterated amine 1.F inally,t he catalytic cycle is closed through aS ET from the reduced Ir II speciest ot he thiol radical( E 1/2 {Ir III /Ir II } = À1.42 Vand E 1/2 {thiol} %À0.85 V), [19] enabling the regeneration of Ir III and the thiolate anion. With the need for as trong base like BTMG to achieve a high deuterium incorporation (see Ta ble 1, Figure 2A), we hypothesize that this pathway,w hichi sc onsistent with previously described mechanistic explanations that have been reported for similars tructures, [15] is more likely than an alternative pathway for the formation of the a-amino radical which would involve aH AT process with the thiol radical.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…This amine is then oxidized via as ingle electron transfer (SET) from the excited photocatalyst (E 1/2 {*Ir III /Ir II } =+1.51 Vand E 1/2 {nBuNH 2 } % + 1.40 V) [18] to generatet he a-amino radical 5, which then undergoes aH AT process with the deuterated thiol (generated in situ) to form the deuterated amine 1.F inally,t he catalytic cycle is closed through aS ET from the reduced Ir II speciest ot he thiol radical( E 1/2 {Ir III /Ir II } = À1.42 Vand E 1/2 {thiol} %À0.85 V), [19] enabling the regeneration of Ir III and the thiolate anion. With the need for as trong base like BTMG to achieve a high deuterium incorporation (see Ta ble 1, Figure 2A), we hypothesize that this pathway,w hichi sc onsistent with previously described mechanistic explanations that have been reported for similars tructures, [15] is more likely than an alternative pathway for the formation of the a-amino radical which would involve aH AT process with the thiol radical.…”
Section: Introductionsupporting
confidence: 81%
“…A major breakthrough towards as implified and easy to use HIE protocol, using photoredox-mediated activation, was reported by MacMillan et al in 2017 [14] detailing the deuteration and tritiation of complex tertiary amines at the a-position to the nitrogen, with good to high selectivity.M ore recently,W ue tal. have reported ap rocedure for the deuteration of silanes, using ap hotoredox-catalyzed polarity-matched hydrogena tom transfer (HAT) with thiols, [15] and this year Wang et al have developedabiphasic protocol, using at ungsten complex as a photocatalyst for the deuteration of aromatic and aliphatic aldehydes. [16] To the best of our knowledge,t hese are the only examples reported so far which combinet he principles of photoredox-catalysis and HIE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of excess amounts of D 2 O, the H/D exchange of the thiol catalyst leads to dominant formation of deuterated thiol. 18 The carbon radical abstracts a deuterium atom from the deuterated thiol to deliver the desired deuterated product and a thiyl radical. A single electron transfer between the thiyl radical and [W 10 O 32 ] 5À H + would regenerate the TBADT catalyst and deuterated thiol aer deuteration with D 2 O.…”
Section: Mechanism Studiesmentioning
confidence: 99%
“…17 Our lab has reported a related visible-light-mediated deuteration of silanes using D 2 O as the deuterium source through the synergistic effect of a photoredox catalyst and a thiol catalyst. 18 However, the substrate scope of photoredox catalyzed C(sp 3 )-H functionalization is limited, because it is successful only when the redox potential of the C-H substrate is matched with that of the photocatalyst. 19 Wang et al have recently reported a H/D exchange at formyl groups of both aromatic and aliphatic aldehydes, by merging a photoredox catalyst, a hydrogen atom transfer (HAT) catalyst, and a thiol catalyst.…”
Section: Introductionmentioning
confidence: 99%